Comparative proteomics of the vector Dermacentor reticulatus revealed differentially regulated proteins associated with pathogen transmission in response to laboratory infection with Rickettsia slovaca - Flores-Ramirez, Gabriela; Sallay, Balázs; Danchenko, Maksym; Lakhneko, Olha; Špitalská, Eva; Skultety, Ludovit (Parasites & vectors, 2019)
BACKGROUND: Tick-borne rickettsial diseases are caused by pathogens acquired from hard ticks. In particular, Rickettsia slovaca, a zoonotic infectious bacterium causing tick-borne lymphadenopathy (TIBOLA), is transmitted by the vectors Dermacentor spp. that can be found all over Europe. Although recent studies point out the extreme complexity of bacteria-induced effects in these blood-feeding vectors, the knowledge of individual molecules involved in the preservation and transmission of the pathogen is still limited. System biology tools, including proteomics, may contribute greatly to the understanding of pathogen-tick-host interactions. METHODS: Herein, we performed a comparative proteomics study of the tick vector Dermacentor reticulatus that was experimentally infected with the endosymbiotic bacterium R. slovaca. Rickettsia-free ticks, collected in the southern region of Slovakia, were infected with the bacterium by a capillary tube-feeding system, and the dynamics of infection was assessed by quantitative PCR method after 5, 10, 15 and 27 days. RESULTS: At the stage of controlled proliferation (at 27 dpi), 33 (from 481 profiled) differentially abundant protein spots were detected on a two-dimensional gel. From the aforementioned protein spots, 21 were successfully identified by tandem mass spectrometry. CONCLUSIONS: Although a few discovered proteins were described as having structural or housekeeping functions, the vast majority of the affected proteins were suggested to be essential for tick attachment and feeding on the host, host immune system evasion and defensive response modulation to ensure successful pathogen transmission.
Keywords: Animals; rickettsiové infekce; Rickettsia; Female; Tick vector; Tick-Borne Diseases; polymerázová řetězová reakce; Polymerase Chain Reaction; ženské pohlaví; DNA bakterií; Protective antigens; Disease Vectors; DNA, Bacterial; Slovakia; Comparative proteomics; proteomika; Rickettsia Infections; nemoci přenášené klíšťaty; Dermacentor; Blood-feeding; Immune modulation; Proteomics; infekce přenášené vektorem; Slovenská republika; zvířata; TIBOLA; Bacterial transmission